Highly Efficient Amplitude Modulation of Terahertz Fano Resonance Based on Si Photoactive Substrate by Low Power Continuous Wave. Issue 12 (1st November 2020) - Zhang, Ming; Zhang, Fenglin; Li, Ming; Li, Peng; Li, Jitao; Li, Jie; Yang, Dingyu
Abstract: It is one of the effective methods to modulate Fano resonance intensity by adding the thin photoactive material in the Fano metadevice and then light pumping them. However, most photoactive materials not only depend on high power femtosecond pulse, but also violently destroy the initial Fano resonance, thus deteriorating the modulated amplitude range (less than 0.35 in previous reports). This study introduces a terahertz (THz) Fano resonator based on Si photoactive substrate (SPS) which is modulated by low power 1064 nm continuous wave without additional photoactive materials. 90% modulation depth and the 0.45 modulated amplitude range are obtained by this device with only 2 mW (0.064 W cm −2 ) pump power. Meanwhile, this study also perfectly solves a long‐neglected problem, i.e., the Fano resonance amplitude of the whole sample seriously deviates from the Au metasurface. At first, the influence of SPS thickness on Fano resonance is investigated, which reveals that SPS thickness low to 3–0.5 µm is required in order to achieve basically the same between Fano resonance of the whole sample and the Au metasurface. And this device shows sharper initial Fano resonance and obtains a higher modulation amplitude range of 0.65 at this time. Abstract : Terahertz Fano resonator based on Si photoactive substrate (SPS) is modulated by low power 1064 nm continuous wave. With optimizing SPS thickness below 3 µm, the modulated amplitude range is as high as 0.65 at 90% modulation depth. The preparation of the thin SPS is suggested to use backside etching Si or silicon‐on‐insulator method.